Renal Function Assessment Gap in Clinical Practice: An Awkward Truth - Francesco Trevisani; Federico Di Marco; Umberto Capitanio; Alessandro Larcher; Arianna Bettiga; Flaviano Dosio; Michele Ghidini; Gianluca Del Conte; Riccardo Vago; Alessandra Cinque; Luigi Gianolli; Andrea Salonia; et al. (Kidney & Blood Pressure Research, 2020)
Introduction: An accurate assessment of renal function is needed in the majority of clinical settings. Unfortunately, the most used estimated glomerular filtration rate (eGFR) formulas are affected by significant errors in comparison to gold standards methods of measured GFR (mGFR). Objective: The objective of the study is to determine the extent of the error of eGFR formulas compared to the mGFR in different specific clinical settings. Methods: A total retrospectively consecutive cohort of 1,320 patients (pts) enrolled in 2 different European Hospitals (Center 1: 470 pts; Center 2: 850 pts) was collected in order to compare the most common eGFR formulas used by physicians with the most widespread mGFR methods in daily clinical practice (Iohexol Plasma Clearance -Center 1 [mGFR-iox] and Renal Scintigraphy -Center 2 [mGFR-scnt]). The study cohort was composed by urological, oncological, and nephrological pts. The agreement between eGFR and mGFR was evaluated using bias (as median of difference), precision (as interquartile range of difference) accuracy (as P30), and total deviation index. Results: The most accurate eGFR formula in the comparison with gold standard method (Iohexol plasma clearance) in Center 1 was represented by s-creatinine and cystatin C combined Chronic Kidney Disease-Epidemiology Collaboration-cr-cy, even though the P30 is reduced (84%) under the threshold of 60 mL/min/1.73 m2. Similar results were found in Center 2, with a wider discrepancy between mGFR-scnt and eGFR formulas due to the minor accuracy of the nuclear tool in respect to the mGFR-iox. Conclusions: The loss of accuracy observed for the formulas at lower values of GFR suggests the mandatory use of gold standards methods as Iohexol Plasma Clearance to assess the correct status of renal function for critical cases. The center 2 showed lower levels of agreement between mGFR and eGFR suggesting that the errors are partially accounted for the Renal Scintigraphy technique too. In particular, we suggest the use of mGFR-iox in oncological urological and nephrological pts with an eGFR lower than 60 mL/min/1.73 m2.